2016
DOI: 10.3390/w8060221
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TRMM 3B43 Precipitation Data for Drought Monitoring in Jiangsu Province, China

Abstract: Satellite-based precipitation monitoring at high spatial resolution is crucial for assessing the water and energy cycles at the global and regional scale. Based on the recently released 7th version of the Multi-satellite Precipitation Analysis (TMPA) product of the Tropical Rainfall Measuring Mission (TRMM), and the monthly precipitation data (3B43) are evaluated using observed monthly precipitation from 65 meteorological stations in Jiangsu Province, China, for the period 1998-2014. Additionally, the standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 43 publications
(44 reference statements)
1
30
0
Order By: Relevance
“…As shown in Figure 6, the higher the SPI time-scale, the less stations show good correlation, indicating that the TMPA-3B43 performed better on a shorter SPI time-scale. This finding is similar to that of Tao et al [22] who found that the TMPA-3B43 had poorer performance with increases of SPI time-scales over the Jiangsu Province, China. This could be due to large RMSE values in longer time-scales, e.g., the seasonal scale RMSE value is greater than the monthly scale (Figure 2).…”
Section: Spi Validationsupporting
confidence: 91%
See 1 more Smart Citation
“…As shown in Figure 6, the higher the SPI time-scale, the less stations show good correlation, indicating that the TMPA-3B43 performed better on a shorter SPI time-scale. This finding is similar to that of Tao et al [22] who found that the TMPA-3B43 had poorer performance with increases of SPI time-scales over the Jiangsu Province, China. This could be due to large RMSE values in longer time-scales, e.g., the seasonal scale RMSE value is greater than the monthly scale (Figure 2).…”
Section: Spi Validationsupporting
confidence: 91%
“…A series of popular statistical metrics such as root mean square error (RMSE), Pearson linear correlation coefficient (R) and relative bias (Bias) are used in this study as listed in Table 2 [22,39,43,44]. The RMSE measures the magnitude of the difference between two variables (e.g., observed precipitation and TMPA-3B43 precipitation).…”
Section: Discussionmentioning
confidence: 99%
“…Werren et al, 2016;Hong et al, 2007) and droughts (e.g. Tao et al, 2016;AghaKouchak et al, 2015;Zhang and Jia, 2013;Naumann et al, 2012). Reliable information on the spatio-temporal variability of rainfall is also one of the main factors to achieve food security, in particular in data-scarce regions (Kang et al, 2009;Verdin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since the province is flat and not suitable for constructing dams or large reservoirs, it is difficult to retain transitional and local surface water. Poor capacity in regulating or storing water has led to insufficient supplies of water [30,31] with seasonal and regional water shortages often occurring in dry years.…”
Section: Description Of Studied Areamentioning
confidence: 99%